2017
DOI: 10.1007/s12192-017-0793-x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of heat shock protein 70 by siRNA enhances the antitumor effects of cisplatin in cultured human osteosarcoma cells

Abstract: Although advances in chemotherapy have improved the prognosis for osteosarcoma, some patients do not respond sufficiently to treatment. Heat shock protein 70 (Hsp70) is expressed at high levels in cancer cells and attenuates the therapeutic efficacy of anticancer agents, resulting in a poorer prognosis. This study investigated whether small interfering RNA (siRNA)-mediated inhibition of Hsp70 expression in an osteosarcoma cell line would enhance sensitivity to cisplatin. The expression of Hsp70 with cisplatin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…1 – 3 , HSP70 overexpression decreased cisplatin-induced HGC-27 cell apoptosis, while inhibition of HSP70 using a specific inhibitor or by transfection of specific shRNA enhanced the cellular apoptosis induced by cisplatin. The present results are consistent with the study of Mori et al ( 14 ). In addition, Liu et al ( 2 ) reported that an HSP70 inhibitor combined with cisplatin suppresses cervical cancer cell proliferation and transplanted tumor growth.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…1 – 3 , HSP70 overexpression decreased cisplatin-induced HGC-27 cell apoptosis, while inhibition of HSP70 using a specific inhibitor or by transfection of specific shRNA enhanced the cellular apoptosis induced by cisplatin. The present results are consistent with the study of Mori et al ( 14 ). In addition, Liu et al ( 2 ) reported that an HSP70 inhibitor combined with cisplatin suppresses cervical cancer cell proliferation and transplanted tumor growth.…”
Section: Discussionsupporting
confidence: 94%
“…As a member of this family, HSP70 has been reported to be highly expressed in different types of cancer ( 6 ) and is considered to be a negative prognostic factor in breast cancer, osteosarcoma and bladder cancer. By contrast, it has been reported as a positive prognostic factor in esophageal, pancreatic and renal cancers ( 14 - 16 ). Recently, multiple studies have demonstrated that HSP70 is involved in resistance to anticancer agents in tumors ( 14 , 17 , 18 ); however, the molecular mechanism of its action in resistance to chemotherapy remains unclear.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…HSPs are chaperone proteins induced by a variety of different stresses. As a member of this family, HSP70 is highly expressed in a variety of cancers and correlated with tumor grade, metastasis, poor prognosis, and chemo-resistance (Behnsawy et al 2013;Daugaard et al 2007;Kumar et al 2016;Mori et al 2017;Yang et al 2012;Yoshidomi et al 2014). In the current study, we found that HSP70 was one of the most important HSPs induced by bortezomib and demonstrated that targeting HSP70 in combination with bortezomib could synergistically induce cytotoxicity, therefore improving the efficacy of MM treatment.…”
Section: Discussionmentioning
confidence: 99%
“…JUN, in turn, is able to bind the promoter region of miR-223, promoting its transcription. HSP70 thus participates in the CIS resistance mechanism in OS cells [ 121 , 122 ].…”
Section: The Different Roles Played By Hsps In Os and Their Therapeutic Benefitsmentioning
confidence: 99%